METODE TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN KABUPATEN KAMPAR - Ali Akbar; Hidayatullah Hidayatullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This paper discusses the Method of Tahfidz Al-Quran at the Boarding Schools in the Regency of Kampar. The method used in fostering students at the Boarding Schools of this Regency was the focus of this study. It was a qualitative approach which was conducted at the Boarding School of Daarun Nahdhah, Al-Badr, the Ansar al-Sunnah, Daar al-Salafi, Sabil al-Salam and al-Taufik. Interview, documentation and observation were the instrumentations used in this study. It was found that the boarding schools in the regency of Kampar used various methods in nurturing students to employ activities of tahfizd al-Qur’an, by means of reading carefully and repeatedly to memorize verse-by-verse without neglecting the Mushaf (annadzar), memorizing verse-by-verse over and over and finally the students could learn by heart (al-Wahdah), depositing or listening what the students had newly been memorized to a teacher (talaqqi), memorizing piecemeal of the Qur’anic verses and read the verses repeatedly (takrir) and listening the memorized verses to others, i.g. both to friends and other congregation (tasmi’)